Changes in iron content, lipid peroxidation, and ferroptosis-related gene expression in vascular endothelial cells in vitro induced by vibration - Siheng WU; Qingsong CHEN; Yingshan ZENG; Yun XIA; Hongyu YANG (环境与职业医学, 2024)
BackgroundVascular endothelial injury is an important pathogenic step of vibration-induced hand arm vibration disease (HAVD), and long-term vibration exposure can lead to vascular endothelial cell dysfunction and cell damage. Cell ferroptosis may be one of the important mechanisms of vibration-induced vascular endothelial cell injury and HAVD. ObjectiveTo explore whether vibration can induce changes in ferroptosis-related indicators in vascular endothelial cells in vitro. MethodsHuman umbilical vein endothelial cells (HUVEC) were divided into four vibrationgroups and two control groups. The vibration groups were exposed to an vibration setting of 125 Hz, 6.5 m·s−2 frequency band and for different durations: 1 d 2 h (total 1 d, 2 h per day), 1 d 4 h (total 1 d, 4 h per day), 2 d 2 h (total 2 d, 2 h per day), and 2 d 4 h (total 2 d, 4 h per day), respectively. All control groups were treated the same as the experimental groups except no vibration exposure. When the cells were 80% confluent, the control groups and the corresponding experimental groups were harvested at the same time. The effects of subgroup treatments on iron, reduced glutathione (GSH), and malondialdehyde (MDA) in HUVEC were detected with a cell ferrous colorimetric test kit, a reduced GSH colorimetric test kit, and a trace MDA test kit, respectively. Real-time quantitative polymerase chain reaction (RT-PCR) was used to detect the mRNA expressions of ferroptosis-related genes acyl-CoA synthetase long chain family member 4 (ACSL4), tumor protein 53 (P53), recombinant human ferritin heavy chain (FTH1), and glutathione peroxidase 4 (GPX4). Western blot (WB) was used to detect the expression levels of ferroptosis-related proteins in HUVEC. ResultsCompared with the control groups, the vibration induced an increase in the iron content of HUVEC with a dose-response trend. Compared with the control groups, the reduced GSH content of HUVEC in the vibration group decreased with the increase of vibration time and frequency, and there was a dose-response trend. Compared with the control groups, the intracellular MDA content of HUVEC in the 1 d 2 h, 1 d 4 h, and 2 d 4 h vibration groups increased, and the MDA content in the 1 d 2 h and 1 d 4 h vibration group increased with time. The RT-PCR results showed that the mRNA expression levels of ACSL4 and P53 in the 1 d 4 h group increased compared with the 1 d 2 h group. Compared with the 2 d control group, the mRNA expression levels of ACSL4 in the 2 d 2 h vibration group and the 2 d 4 h vibration group increased, and the mRNA expression level of P53 in the 2 d 4 h vibration group increased. Compared with the 1 d control group, the mRNA expression levels of FTH1 and GPX4 in endothelial cells in the vibration 1 d 2 h group decreased. The WB results showed that compared with the control groups, the expression level of ferroptosis-related protein ACSL4 in endothelial cells increased in the vibration 1 d 2 h group; the expression levels of P53 in the 1 d 2 h and 2 d 4 h vibration groups increased; the expression levels of GPX4 decreased in the 1 d 4 h and 2 d 2 h vibration group, and the decrease was more obvious in the 2 d 2 h vibration group than in the 1 d 2 h vibration group; the above differences were statistically significant (P<0.05). ConclusionVibration induces an increase in iron content, a decrease in GSH, and an increase in MDA in vascular endothelial cells in vitro, as well as mRNA and protein expressions of ferroptosis-related genes ACSL4, P53, FTH1, and GPX4.